2005
DOI: 10.1021/jf0506737
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Resveratrol in Peanut Kernels by Application of Abiotic Stresses

Abstract: Application of no postharvest stress or by size reduction, grinding, chopping, or slicing and exposure to UV light or ultrasound were investigated for the elicitation of trans-resveratrol, total phenolic compounds, and antioxidant activity (AOA) in peanut kernels. AOA and total phenolic compounds did not increase in stressed peanuts over incubation times 0-48 h at 25 degrees C; however, an increase in trans-resveratrol concentration over time occurred. Slicing (2 mm), ultrasound exposure for 4 min at 25 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 35 publications
4
58
2
Order By: Relevance
“…Chiron et al (2000b) and Chung et al (2001) revealed that wounding caused by a mock fungal inoculation or leaf punching resulted in the induction of the stilbene biosynthesis genes in Scots pine (STS, PMT) and peanut (STS), respectively. Rudolf and Resurreccion (2005) found that slicing of peanut kernels increased production of t-resveratrol. Harju et al (2009) report that wounding caused by drilling holes through the stem of Scots pine induced the production of pinosylvin and pinosylvin monomethyl ether.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…Chiron et al (2000b) and Chung et al (2001) revealed that wounding caused by a mock fungal inoculation or leaf punching resulted in the induction of the stilbene biosynthesis genes in Scots pine (STS, PMT) and peanut (STS), respectively. Rudolf and Resurreccion (2005) found that slicing of peanut kernels increased production of t-resveratrol. Harju et al (2009) report that wounding caused by drilling holes through the stem of Scots pine induced the production of pinosylvin and pinosylvin monomethyl ether.…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…There were also increase and decrease in the amounts of resveratrol in response to ultrasonication treatment and incubation time reported in peanut kernels. Specifically, a significant increase in resveratrol concentrations was shown in ultrasonication-treated peanut kernels after 24 h of incubation in the dark, but a decrease occurred after incubation for 24-36 h (Rudolf and Resurreccion, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, ultrasonicationed to a 60-70% increase in shikonin yield in Lithospermum erythrorhizon cell culture ), 75% increase in ginsenoside saponins in ginseng cells , and a three-fold increase in taxol in Taxus baccata cell culture (Rezaei et al, 2011). The elicitation of resveratrol by ultrasonication has been extensively studied in whole or sliced peanut kernels, and increases of 8 to 143 times were reported (Potrebko and Resurreccion, 2009;Rudolf and Resurreccion, 2005;Sales and Resurreccion, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some genotypes produced one major phytoalexin component, whereas other genotypes produced several major components. Rudolf and Resurreccion (2005) noted an eightfold increase in trans-resveratrol concentration over time after exposure of peanut kernels to abiotic stress (size reduction by grinding, chopping, or slicing and exposure to UV light or ultrasound). Ultrasound was also shown to increase phytoalexin levels: trans-resveratrol from 0.03 mg/kg (control material) to 2.10-4.73 mg/kg and trans-piceid from 0.07 to 0.23-0.38 mg/kg (Potrebko and Resurreccion, 2009).…”
Section: Stilbenes In Nuts and Almondsmentioning
confidence: 99%